Efficacy and safety of anisodine hydrobromide injection for acute ischemic stroke: a systematic review and meta-analysis - Wang, Yang; Wan, Feng; Hu, Peiqun; He, Benxiang; Hu, Yushi; Liu, Yunlu (Frontiers in Pharmacology, 2023)
Background: Acute ischemic stroke (AIS) is a leading cause of death and disability worldwide. This study aimed to evaluate the efficacy and safety of anisodine hydrobromide (Ani) injection in the treatment of AIS. Methods: Randomized controlled trial (RCTs) based on Ani injection for the treatment of AIS were retrieved from both Chinese and English databases. The retrieval period was from the databases’ inception to May 2023. The Cochrane Collaboration Risk of Bias Tool was used to assess the methodological quality. The outcome indicators were analyzed using RevMan 5.3 software. Results: We included the findings of 11 RCTs encompassing 1337 patients with AIS. Our meta-analysis revealed that Ani injection supplementation significantly reduced the National Institutes of Health Stroke Scale (MD=-1.53, 95%CI=[-1.94,-1.12], p＜0.00001 ), modified Rankin Scale (MD=-0.89, 95%CI=[-0.97,-0.81], p＜0.00001), and the relative time to peak (SMD=-0.81, 95%CI= [-1.08,-0.55], p＜0.00001) significantly. Additionally, Ani injection significantly increased the Barthel Index (MD=10.65, 95%CI= [4.30,17.00], p=0.001), relative cerebral blood volume (SMD=0.28, 95%CI= [0.02,0.53], p=0.03), and clinical efficacy (RR=1.2, 95%CI= [1.08,1.34], p=0.001). No statistically significant difference in the rate of adverse events was observed between the Ani injection supplemental group and the control group. Conclusion: Based on currently published evidence, Ani injection was found to be effective and safe in improving AIS outcome. Nevertheless, limitations of the included RCTs still exist, and thus, more multi-center, large sample, high-quality RCTs are required to further verify the efficacy and safety of Ani injection in patients with AIS.